Idiopathic Hypersomnia Patients Revealed Longer Circadian Period Length in Peripheral Skin Fibroblasts - Materna, Linus; Halfter, Hartmut; Heidbreder, Anna; Boentert, Matthias; Lippert, Julian; Koch, Raphael; Young, Peter (Frontiers in Neurology, 2018)
The vast majority of living organisms have evolved a circadian rhythm of roughly 24 h in adaptation to ever-changing environmental conditions, such as the cycle of light and darkness. In some sleep disorders like idiopathic hypersomnia (IH) this adaptation is defective. As the etiology of this disease is largely unknown, we examined the in vitro circadian period length of patients suffering from IH. The patients were diagnosed according to the ICSD3-criteria by clinical history, polysomnography (PSG), and multiple sleep latency testing (MSLT). In order to gain insight into the molecular mechanism of this sleep disorder we collected fibroblasts from skin biopsies of IH patients and healthy subjects. We determined the circadian period length of the primary fibroblast cells by lentiviral infection with a construct expressing a luciferase gene under the control of a BMAL1 promoter. The group of IH patients revealed on average a prolonged circadian period length. In comparison to the group of healthy controls (HC) the mean period length was estimated to be 0.82 h (95%-CI 0.44–1.20 h) longer in the patient group. This finding further stresses a disturbed regulation of the circadian rhythm in IH patients as part of the pathophysiology of this complex and poorly understood primary sleep disorder.